Imaginação e teologia: o potencial criativo da linguagem aplicado ao fazer teológico - contribuições de Paul Ricoeur - Souza, Marcelo Henrique de (2023)
This research investigates the theological epistemology and methodology in light of imagination theory elaborated by the french philosopher Paul Ricoeur. Born in protestant tradition, his studies by language philosophy, particularly about metaphor and narrative, and the application of them in the theology sphere, especially in the biblical hermeneutic, assured him a range beyond his faith community. Studied by philosophers and hermeneuts, biblical scholars and systematic theologians, Ricoeur is an encounter point of many knowledges and an opportune work in contends and methods to the theological work. One of his theorical production is the imagination, understanded like transcendental faculty, like language potential and like condition to the advance of speculative-conceptual thinking. His metaphor theory is the privileged place to articulate the wide notion of imagination like human capacity with the specifical notion of it like poetic of language, like creation of signifies and discover of world aspects by the way of discourses vitality. It’s possible, with Ricoeur, to constate the presence of one metaphoric in the religious discourse, particularly in the biblical language, that inaugurates one textual hermeneutic that, in turn, opens the way to the work properly speculative of Cristian theology. Thereby, one imaginal theology, that is, one theology crossed by the various aspects of imagination (imagens, creativity, human faculty, poetic of language, etc.), can emerge grounded on the Paul Ricoeur’s theories. After study the itinerary that carries the philosopher by the linguistic and philosophical considerations to the hermeneutic and speculative practices on theology, some ways can be proposed to the edification of one imaginal theology on three of its big areas: fundamental, biblical and systematic